Idea of Universal Music in Romantic and Neodaoist Cultures - Motiekaitis, Ramūnas (Acta Orientalia Vilnensia, 2002)
The article deals with Romanticism and Daoism that from the first view have many similar features. Both of them are orientated to individualism, naturalism, aesthetism, iracionalism, paradoxes and the feeling of ephemeral existence. All these diversities are unified by universal origins such as “spirit” (Geist) or dao where one of the main ways of integration between individual and universal is via aesthetical sphere. This implies some similar aesthetical discourses.The article compares the ideas of universal music by German idealists and early Romantics with Neodaoist aesthetics of instrument qin. Universal music as a wide metaphor used by many philosophers reflects ideas of harmonious cosmos and at the same time shows the ways of artistic creativity. The author also observes some aspects of practical music in order to understand how these conceptions reflect musical thinking.Aesthetics of instrument qin is mostly related with Neodaoist ideals, however at the same time it contains many elements of Confucianism, Han naturphilosophy and even Buddhism. In Neodaoist Wang Bi’s philosophy which is based on Laozi, dao is interpreted as pure being or unity substance and function. In aesthetics of qin perfect music or perfect listening also reveals this state of pure being. Therefore, according to aesthetician Xi Kang “music expresses neither happiness nor sadness”. Such attitudes oppose to Confucianist ideas of musical ethos. Ideas of autonomous music or semantic emptiness of music are also found in some German idealist or early Romantics writings. In conceptions of Hegel, SchelIing, Ritter, and Novalis “Absolute Music” is interpreted as symbol of transcendent subject or perfect synthesis while real music as the highest art. These conceptions strongly oppose to previous understanding of music as mimetic or representative art.Attitudes to music as to a phenomenon which reflects or reveals universal origins are distinctive for both, Romanticism and Neodaoism, but ontological structures of these origins and ways of musical reception are different. Program or technical descriptions of qin provide us with many comparisons of music with nature. Various natural phenomena or animals reflect spontaneous actions that are similar to dao. Therefore through observing and imitating them it is possible to obtain their inner state, i. e. being in unity with dao. Program descriptions, various subtle nuanses, and silent tone of qin imply contemplative ways of performing and listening. It is actually much more “resonating” than expression. According to some previous Chinese principles, unity of individual and universal can be achieved via proper listening. In the same way Neodaoist aesthetics of universal dao music is organically realised in the practice of qin.Ideas of “Absolute Music” and musical practice in Romanticism function as antipodes. “Absolute Music” reflects ideas of “synthesis” while teleology of real music is a transcendental subject. The authentic way of listening described by Wackenroder is just listening to sounds and their progresion and avoiding all extramusical meanings. In this case it reminds a Neodaoist way of listening. However, in Romantic context it functions much more like conceptual refrain from really existing in music. Romantic Symphonic or Sonate forms could be described as volitional “travel” from fragmental existence, through returning to nature (the lost paradise) to awakening and triumphal end. Thus that Romantic act of creative integration is excentrically establishing.Universal music as symbol of spirit, or dao, despite some analogies in aesthetical discourses, reflects general differences between Chinese and Western thinking. Romanticism and Neodaoism, therefore, in many points could be interpreted as antipodes.